Prevalence and Clinical Consideration of Anatomical Variants of the Splenic Artery: A Systematic Review and Meta-Analysis - Nova-Baeza, P (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background: The spleen is the largest secondary immune organ in the body. Knowledge regarding the normal splenic vascular anatomy and its anatomical variants is crucial in the medical practice of surgeons and radiologists and is useful for diagnostic evaluations and the guidance of various surgical procedures. Hence, in this research, we aim to characterize the behavior of the lineal or splenic artery in humans from an anatomoclinical point of view. Methods: A systematic search was carried out in electronic databases to compile the available literature on the research subject. Searches were undertaken in the following databases: Medline, Scielo, Wos, Cinahl, Scopus, and Google Scholar. The search terms were “Splenic artery”, “Splenic vascularization”, “Anatomical variations’’, “Splenic organ”, and “Clinical anatomy”. Results: From the 35 studies included in this review, clinical correlations of anatomical variations in the splenic artery with surgical procedures in the abdominal region were reported in 8 studies. These correlations are mainly associated with surgical procedures for the pancreas, liver, stomach, and bile ducts through imaging of the spleen. To verify our conclusions, the risk of bias of the anatomical studies was measured using the AQUA checklist. Conclusions: Recognition of the usual anatomy and anatomical variants of the splenic artery is crucial for both morphology professionals and clinicians addressing the abdominal region and its vascular components. In this review, we determined that the splenic artery could present a variation in its origin or entry into the splenic hilum, which could mean that in any abdominal intervention there may be complications if the splenic artery variation is overlooked. More anatomic clinical studies considering this variation in both diagnostic and surgical processes are suggested for further investigations. © 2023 by the authors.